Improving the moisture resistance and luminescent properties of K2TiF6:Mn4+ by coating with CaF2. (July 2019) - Dong, Qizheng; Guo, Chengjin; He, Ling; Lu, Xuefeng; Yin, Jianbo
Graphical abstract: Highlights: K2 TiF6 :Mn 4+ @CaF2 phosphors were successfully prepared. The luminous intensity of phosphors increased. The moisture resistances of Mn 4+ -doped fluoride phosphors were enhanced. K2 TiF6 :Mn 4+ @CaF2 phosphors have a high stability. Abstract: The moisture resistance and luminescent properties of K2 TiF6 :Mn 4+ (KTF) phosphor was enhanced through a facile coating method to modify its surface, in which CaF2 was used as a coating material. The structure, morphology, and composition of the KTF@CaF2 samples were investigated via power X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), energy-dispersive X-ray spectroscopy (EDS), scanning electron microscopy (SEM), and transmission electron microscope (TEM). The luminescence properties were identified by luminescence spectra. The results show that, after being treated with CaF2, the surface morphology changed to some extent, and the luminous intensity of phosphor was enhanced. Through application of a moisture resistance test, the luminous intensity of KTF@CaF2 phosphor was maintained, whereas the KTF was hydrolysed and the luminous intensity decreased. This was ascribed to local distortion of the crystalline field around Mn 4+ in phosphors and the improvement of surface moisture resistance of phosphors after coating with CaF2 .